Smart parking for the delivery of goods in urban logistics - Ferreira, J. (2018)
The purpose of this research is to develop an application to reserve slots of loading and unloading activities in urban environment and create a collaborative low cost solution based on BLE (Bluetooth Low Emission) beacons to monitor this process. Violations can be easily detected through a collaborative process among user mobile devices detection and a reward mechanism incentives user participation. This approach allows the implementation of a system to handle parking slots for load and unload of goods, without investments costs using an ad-hoc network of users that sends information to a central system and from this violations were sent to control agents. This solution allows the coordination of the usage of parking places for load/unload of goods in a city environment following European guidelines. The developed App assists operators towards parking place with routing and traffic advice and collects data for mobility authorities.